Agronomic management of early maturing soybeans in North Carolina. Issue 2 (20th September 2021) - Gross, MaKayla Raquel; Vann, Rachel; Brown, Austin; Formella, Adam; Gibbs, Andrea; Gurganus, Rod; Heiniger, Ryan; Hurry, Jarette; Jordan, David; Leary, Matthew; Lilley, Dylan; Malloy, Mac; et al.
Abstract: Interest in producing indeterminate, early maturing soybean [ Glycine max (L.) Merr.] varieties [maturity group (MG) ≤IV] has increased in the southeastern United States as producers seek ways to increase soybean yields. The objective of this experiment was to generate agronomic management recommendations for early maturing soybean varieties across the southeastern United States and compare these management recommendations to historical recommendations for later‐maturing varieties through identification of the optimal seeding rates, row spacing, planting dates, and fertility management. Experiments were conducted across North Carolina at seven environments in 2018 and at four environments in 2019. Two MGs were used in this study: MG III and MG IV. Data on soybean yield and soybean seed quality were collected. Row spacing recommendations were similar to recommendations for later‐maturing varieties with narrow rows providing a 7.3 bu acre –1 yield advantage across environments on average, with more pronounced yield advantages in high‐yield environments. Seeding rate impacted soybean yield but not seed quality. An economic analysis was conducted for seeding rate, suggesting that 80, 000 to 120, 000 seeds per acre will optimize both profit and yield across environments with May planting. Planting date sometimes impacted yield and seed quality, suggesting that earlier planting with these varieties could be critical to optimizing soybean yield and seed quality. Fertility applications at R1 (beginning of flowering) did not have an impact on soybean yield or seed quality. Core Ideas: Narrow rows (15–18 inches) gave a 7.3 bu acre –1 yield advantage over wide rows (30–36 inches). Seeding rates of 80, 000 to 120, 000 seeds acre –1 optimized yield and profit for May planting. Earlier planting dates often led to higher yields and impacted seed quality. Despite heavy nutrient demand, fertilizer application at the R1 stage did not impact yield.